Sistemas redox reversíveis Fe°/óxido de ferro para produção de hidrogênio - Marcelo Goncalves Rosmaninho (2010)
Hydrogen is the fuel of future, due to its energetic efficiency and the environmental aspects. The most important current challenges are to develop efficient methods to produce hydrogen and find safe, simple and low cost forms to store and transport the H2 gas. In this workit was investigated a new system for hydrogen production using renewable and/or low cost and environmental impact fuels, like ethanol, natural gas or solar radiation. This system is based ontwo reversible reactions involving Fe and iron oxides. In the first reaction the iron oxide reacts with the fuel, e.g. ethanol, to produce metallic iron, and in a second step the produced iron is reoxidized using water, producing hydrogen. The work is divided into four parts:(i) Synthesis and characterization of the iron oxides -Fe2O3, -Fe2O3, Fe3O4, -FeOOH, following by reduction in Temperature Programmed Reaction (TPRe) experiments. The results showed that ethanol reduces the different iron oxides. XRD, Msbauer, TG/DTA and SEManalysis, as well as the reactions carried out at 300, 400, 500, 600, 700, 800 and 900 C suggested the formation of the different products depending on the temperature: Fe3O4 at 300 C, Fe1-xO at500 C, Fe at 600 C and Fe3C at temperatures higher than 600 C, as well as carbon deposition. (ii) Synthesis and characterization of iron oxides composites supported on Al2O3, SiO2 and TiO2 with 7, 14, 21 e 35 wt% of iron. The supported iron oxides are reduced in a similar wayto the pure oxides. However, iron reacted with the SiO2 and TiO2 support to form more stable oxides. (iii) Study of redox cycles using hydrogen and also ethanol for the reduction of the iron oxides supported and unsupported, following of the oxidation with water. Both the pure hematiteand the alumina-supported iron oxides showed activity for at least five consecutive reduction/oxidation cycles. The supported iron oxides were significantly more active during reduction/oxidation cycles.(iv) Use of Ni ferrites in redox cycles similar to the previous ones, but using thermal reduction of the ferrites at temperatures up to 1400 C , following by oxidation with water up to 1200 °C , simulating the condition used in a solar reactor. The samples were characterized byTPR, TPO, SEM, XRD, ICP and XPS, and submitted to thermal reduction and water splitting cycles. The results showed that the completely substituted ferrite (NiFe2O4) is more easily reduced, as well shows higher stability when submitted to multiple redox cycles. However, thesupported ferrite showed higher hydrogen production compared to the unsupported one. This part of the work was carried out at the Instituto de Catáisis y Petroleoquímica (ICP) in Madrid